Evaluation of Rhizobium on Birdsfoot Trofoil in acid soil - Brose, Edemar (Pesquisa Agropecuaria Brasileira, 1992)
Sixteen strains of  loti were tested on birds foot trefoil (Lotus comiculatus L.) cv. São Gabriel in a greenhouse with a Haplohumox soil (Vacaria unit). After liming, the soil showed pH 5.1, P 6.5 ppm and Al lowered to 0.9 meq/100 g. In the laboratory, 14 strains were tested for their growth ability on two levels of pH (4.9 and 4.5) and five levels of Al (0, 50, 100, 150 and 300 11 ). The strains recommended for inoculant production, SEMIA 806 and SEMIA 816, were used as controls. The strains EEL 3484, EEL 11184 and EEL 17384 were the most susceptible to Al at pH 4.9 and 4.5 and were associated with low dry matter yield and total plant N in the greenhouse experiment. The strains EEL 13484, EEL 13584 and EEL 17384 had the best performance in terms of dry matter (DM) production as compared to the controls SEMIA 806 and SEMIA 816, although the differences observed were not statistically significant.